Faktor Yang Berhubungan Dengan Perilaku Ibu Hamil Dalam Pencegahan Preeklampsia Di Wilayah Kerja Puskesmas Kandanghaur Kabupaten Indramayu Tahun 2023 - Wahyudin, Wahyudin; Rudiansyah, Rudiansyah; Fifih, Fifih; Widyastuti, Setyo Dwi (JURNAL KESEHATAN INDRA HUSADA, 2023)
The Maternal Mortality Rate is an indicator to see the success of maternal health efforts. The main complications that cause mothers to die in almost 75% of all maternal deaths are bleeding, high blood pressure (preeclampsia and eclampsia), and infection. Based on the Indramayu District Health Profile in 2021, the highest maternal mortality is caused by hypertension in pregnancy (preeclampsia/eclampsia). Preeclampsia can occur due to unfavorable behavior of pregnant women. The purpose of this study was to determine the factors associated with the behavior of pregnant women in the prevention of preeclampsia. This study used an analytic method with a cross-sectional approach, population in this study was 734 pregnant women, and the sample 85 respondents, was taken using an accidental sampling technique. The instrument used is a questionnaire. Test the hypothesis using the Chi-square test. The results showed that the variables related to the behavior of pregnant women in preventing preeclampsia were knowledge (P=0.0001), attitude (P=0.0001), support from health workers (0.0001), and husband support (P= 0.020) ). Meanwhile, the variable that was not related to the behavior of pregnant women in preventing preeclampsia was access to health services (P=0.108). Conclusion There is a relationship between the variables of knowledge, attitudes, support from health workers, and husband's support with the behavior of pregnant women in preventing preeclampsia. This research suggestion is aimed at pregnant women so they can increase their knowledge by participating in counseling and increasing positive behavior by carrying out routine pregnancy checks.